1997
DOI: 10.1090/s0002-9939-97-03692-7
|View full text |Cite
|
Sign up to set email alerts
|

General helices and a theorem of Lancret

Abstract: Abstract. We present a theorem of Lancret for general helices in a 3-dimensional real-space-form which gives a relevant difference between hyperbolic and spherical geometries. Then we study two classical problems for general helices in the 3-sphere: the problem of solving natural equations and the closed curve problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(99 citation statements)
references
References 7 publications
0
99
0
Order By: Relevance
“…">IntroductionMany authors have made significant contributions to the theory of curves from past to present. Some of these studies indicated that the relationships between the curvatures of the space curves are quite remarkable, and the new special curves are also defined via these relations [1][2][3][4][5]. Helices, one of these special space curves, have been studied by many researchers [6][7][8][9].…”
mentioning
confidence: 99%
“…">IntroductionMany authors have made significant contributions to the theory of curves from past to present. Some of these studies indicated that the relationships between the curvatures of the space curves are quite remarkable, and the new special curves are also defined via these relations [1][2][3][4][5]. Helices, one of these special space curves, have been studied by many researchers [6][7][8][9].…”
mentioning
confidence: 99%
“…In [4], the second author used the concept of Killing vector field along a curve to define the notion of general helix in a three dimensional real space form, M(C). Then, he obtained the extension of the Lancret program to this framework.…”
Section: The Extended Lancret Programmentioning
confidence: 99%
“…The well-known characterizations obtained for a single curve have allowed to define some special curves such as helix, slant helix, plane curve, spherical curve, etc. [1,11,13,20,23] and these special curves, especially helices, are used in many applications [2,9,10,19]. Similarly, by considering two curves, some special curve pairs such as involute-evolute curves, Bertrand curves, Mannheim curves have been defined and studied so far [4,12,14,15,18,21,22].…”
Section: Introductionmentioning
confidence: 99%